(untitled) (Bangladesh Journal of Public Administration, 2019)
The study was conducted to identify the reasons behind girl‟s dropout from school in rural areas of Bangladesh and understand the problem to find out possible solutions. A questionnaire survey, case study and focus group discussion were selected as study instrumentations which were administered at Golna Union of Saidpur Upazila of Nilphamari district. The study identified some socio-cultural and economic reasons behind the girl‟s dropout problem. Economic vulnerability of the families was the primary reason identified behind the problem. Some other problems identified are like dowry, child marriage, the unemployment problem, tendencies to get a job at Uttara Export Processing Zone (UEZP) and, insufficient cash support for continuing study. Creating job opportunities through industrialization and transferring extra agricultural labour were identified as the best possible solutions. Also, immediate steps against the dowry system and child marriage, guide book and tuition study system, engaging Non-Government Organizations (NGOs) in development activities have been recommended to mitigate the problem. Solving girl‟s dropout problem warrants a holistic approach, engaging all the possible stakeholders to build a quality education system and a socio-economically transformed society for the future generation.